The Possible Role of the Uropygial Gland on Mate Choice in Domestic Chicken - Hirao, Atsushi (International Journal of Zoology, 2011)
In avian mating systems, male domestic fowls are polygamous and mate with a number of selected members of the opposite sex. The factors that influence mating preference are considered to be visual cues. However, several studies have indicated that chemosensory cues also affect socio-sexual behavior, including mate choice and individual recognition. The female uropygial gland appears to provide odor for mate choice, as uropygial gland secretions are specific to individual body odor. Chicken olfactory bulbs possess efferent projections to the nucleus taeniae that are involved in copulatory behavior. From various reports, it appears that the uropygial gland has the potential to act as the source of social odor cues that dictate mate choice. In this review, evidence for the possible role of the uropygial gland on mate choice in domestic chickens is presented. However, it remains unclear whether a relationship exists between the uropygial gland and major histocompatibility complex-dependent mate choice.